Trapped Factors and China's Impact on Global Growth. Issue 633 (6th July 2020) - Bloom, Nicholas; Romer, Paul; Terry, Stephen J; Van Reenen, John
Abstract: After a recent increase in Chinese import competition, European firms increased innovation. We present and rationalise these patterns using 'trapped factors' at the micro level within a stylised equilibrium model of product-cycle trade and growth. Trade integration of the magnitude observed between the OECD and low-wage nations as a whole can considerably increase the long-run growth rate and welfare. In the short run exposed firms devote trapped factors to increased innovation, leading both to increased innovation at these individual firms as well as to a small amount of extra transitional growth overall. China accounts for half of the dynamic trade gains.